Labor market policies, institutions and employment rates in the EU-27 - Riccardo Rovelli; Randolph Luca Bruno (Institute for the Study of Labor (IZA), 2008)
We compare labor market policies, institutions and outcomes for the EU member states, for the period 2000-2005. We document the main differences in Labor Market Policies across EU members, including new member states after 2004. We focus on indicators of policy generosity (expenditures relative to GDP) and relate these and other policy indicators to indicators of labor market outcomes and performance. Our results show that, on a cross-country basis, higher rates of employment are in general associated with: (i) higher expenditures on labor market policies, especially on active policies for countries with a high pro-work attitude; (ii) a lower degree of rigidity in labor market institutions and in product market regulation.
urn:nbn:de:101:1-20080527222
Keywords: J08; 330; Labor market policies; labor market outcomes; European social models; Arbeitsmarktpolitik; Wirkungsanalyse; Vergleich; Beschäftigungseffekt; Sozialstaat; EU-Staaten